The effects of COVID-19 on maternal, newborn and child health services in Papua New Guinea - Lisa M. Vallely; Jamee Newland; Nalisa Neuendorf; Agnes Kupul Mek; Rachael Farquhar; Zebedee Kerry; Ruthy Boli-Neo; Mikaela Seymour; Melanie Wratten; Herick Aeno; Richard Nake Trumb; Anna Maalsen; et al. (Taylor & Francis Group, 2024)
Papua New Guinea's health system faces ongoing challenges in the provision of maternal and child health and has some of the poorest health indicators in the world. In this paper, we describe the impact of COVID-19 on maternal and child health, as examples of primary health care services. We conducted 131 semi-structured interviews with different population groups in seven provinces (Jul-Nov 2021). A deductive analysis focused on identifying the impact of COVID-19 using the World Health Organization building blocks framework. An inductive analysis explored these impacts for maternal and child health services specifically. We identified three broad themes: service disruption, challenges in access to care and service provision. Service disruption included the closure, suspension and relocation of services and workforce challenges due to healthcare worker absences, redeployment and working within an already constrained health system. Access to care was difficult due to lockdowns and restricted movement. Service provision continued despite the fear staff had of COVID-19. Investing in pandemic preparedness, including an adequately trained and resourced healthcare workforce and facilities able to withstand sustained provision of essential services should be integrated with locally appropriate, and timely community-based information to allay fears and mistrust within the healthcare system.